THE SPECIFIC OF THE INTERPRETATION OF THE CHRISTIAN DOGMA IN THE “THE GREAT KATEHISM” (1627) BY LAVRENTIYU ZUZANIA - Квасюк, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article it is described “The Great Katehism” by Lavrentiyu Zuzania, that was published in Moscow in 1627 year, but it is referred to the period of Kiev art of the Orthodox author; it is demonstrated the structure and possible trousers of the text; it is analyzed the specific of interpretation of the Orthodox dogma as the truth of faith, that was made by the great influence of the western theological system (examining dogma about the Trinity, the godlike human uman nature of Christ, eschatological conception), the protestants sacrament logy , and also was caused by polemical aims – the mass actions against the religious opponents.